Study of rumen metagenome community using qPCR under different diets - Singh, K.M. (Meta Gene, 2014)
The aim of this study was to detect the major bacteria present in rumen microbiota. Here, we performed qPCR based absolute quantitation of selected rumen microbes in rumen fluid of river buffalo adapted to varying proportion of concentrate to roughage diets. Animals were adapted to roughage-to-concentrate ratio in the proportion of 100:00 (T1), 75:25 (T2), 50:50 (T3) and 25:75 (T4) respectively for 30 days. At the end of each treatment, rumen fluid was collected at 0 h and 2 h after feeding. It was found that among fibrolytic bacteria Ruminococcus flavefaciens (2.22 × 10(8) copies/ml) were highest in T2 group and followed by 1.11 × 10(8) copies/ml for Fibrobacter succinogenes (T2), 2.56 × 10(7) copies/ml for Prevotella ruminicola (T1) and 1.25 × 10(7) copies/ml for Ruminococcus albus (T4). In non-fibrolytic bacteria, the Selenomonas ruminantium (2.62 × 10(7) copies/ml) was predominant in group T3 and followed by Treponema bryantii (2.52 × 10(7)copies/ml) in group T1, Ruminobacter amylophilus (1.31 × 10(7)copies/ml) in group T1 and Anaerovibrio lipolytica (2.58 × 10(6) copies/ml) in group T4. It is most notable that R. flavefaciens were the highest in population in the rumen of Surti buffalo fed wheat straw as roughage source.